Autocrine Wnt regulates the survival and genomic stability of embryonic stem cells - Augustin, Iris; Kerr, Grainne; Boutros, Michael (Science signaling, 2017)
Wnt signaling plays an important role in the self-renewal and differentiation of stem cells. The secretion of Wnt ligands requires Evi (also known as Wls). Genetically ablating Evi provides an experimental approach to studying the consequence of depleting all redundant Wnt proteins, and overexpressing Evi enables a nonspecific means of increasing Wnt signaling. We generated Evi-deficient and Evi-overexpressing mouse embryonic stem cells (ESCs) to analyze the role of autocrine Wnt production in self-renewal and differentiation. Self-renewal was reduced in Evi-deficient ESCs and increased in Evi-overexpressing ESCs in the absence of leukemia inhibitory factor, which supports the self-renewal of ESCs. The differentiation of ESCs into cardiomyocytes was enhanced when Evi was overexpressed and teratoma formation and growth of Evi-deficient ESCs in vivo were impaired, indicating that autocrine Wnt ligands were necessary for ESC differentiation and survival. ESCs lacking autocrine Wnt signaling had mitotic defects and showed genomic instability. Together, our study demonstrates that autocrine Wnt secretion is important for the survival, chromosomal stability, differentiation, and tumorigenic potential of ESCs.